다중데이터링크 기반에서 데이터링크 처리기와의 데이터 무결성 보장을 위한 전술상황전시기 간 데이터 기록 및 재생 방법 연구 - 이현주; 정은미; 이성우; 염재걸; 김상준; 박지현; Lee, Hyunju; Jung, Eunmi; Lee, Sungwoo; Yeom, Jaegeol; Kim, Sangjun; Park, Jihyeon ((사)디지털산업정보학회 논문지, 13(2), 2017)
Recently, the high performance of tactical situation display console and tactical data links are used to integrate the operational situations in accordance with information age and NCW (Network Centric Warfare). The tendency to maximize the efficiency of task execution has been developed by sharing information and the state of the battle quickly through complex and diverse information exchange. Tactical data link is a communication system that shares the platform with core components of weapons systems and battlefield situation between the command and control systems to perform a Network Centric Warfare and provides a wide range of tactical data required for decision-making and implementation.It provides the tactical information such as tactical information such as operational information, the identification of the peer, and the target location in real time or near real time in the battlefield situation, and it is operated for the exchange of mass tactical information between the intellectuals by providing common situation recognition and cooperation with joint operations. In this study, still image management, audio file management, tactical screen recording and playback using the storage and playback, NITF (National Imagery Transmission Format) message received from the displayer integrates the tactical situation in three dimensions according to multiple data link operation to suggest ways to ensure data integrity between the data link processor during the entire operation time.